Evaluation of a genetic assay for canine transmissible venereal tumour diagnosis in Brazil - Castro, K. F. [UNESP]; Strakova, A.; Tinucci-Costa, M. [UNESP]; Murchison, E. P. (Wiley-Blackwell, 2017)
The canine transmissible venereal tumour (CTVT) is a transmissible cancer that is spread between dogs by the allogeneic transfer of living cancer cells. The infectious agents in CTVT are the living cancer cells themselves, which are transmitted between dogs during coitus. CTVT first arose several thousand years ago and the disease has a global distribution and is frequently observed in dogs from Brazil. We evaluated the utility of a LINE-MYC quantitative polymerase chain reaction for diagnosis of CTVT cases in Brazil. Our analysis indicated that the LINE-MYC rearrangement was detectable in all CTVT samples but not in their corresponding hosts. This genetic assay proves to be a useful tool for providing a definitive molecular diagnosis of CTVT, which presents with varying degrees of aggressiveness and invasiveness in different host dogs and can therefore be a diagnostic challenge in some specific cases.
Keywords: canine transmissible venereal tumour; LINE-MYC; molecular diagnosis; oncology; transmissible cancer